Peranan Anggaran Partisipatif Dalam Rangka Peningkatan Kinerja Manajerial Dikaitkan Dengan Budaya Organisasi Dan Hubungan Antarindividu Pada Organisasi - Novita Ekasari; Lintang Venusita (AKRUAL: JURNAL AKUNTANSI, 2009)
AbstractThis article aims to provide a framework to think about the role of participatory budgeting to improve managerial performance is associated with organizational culture and relationship between individuals at nonprofit organizations. Participatory budgeting process to function properlyand implemented well, if supported by the device work, human resources, individual relationships within the organization, and culture that has taken hold in a nonprofit organization. Each nonprofit organization aims to improve services and performance-oriented but not profit. Several nonprofit organizations have undergone repositioning and development organization which aims other than to provide services to the community also increases the profits from service operations.